Disability due to leprosy: a socio-demographic study in Leprosy Hospital, Chamba, Himachal Pradesh - Dixit, Pragya; Dhiman, Arvind Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Leprosy is a chronic granulomatous disease caused by M. leprae bacilli and one of the important cause of preventable disability. Methods: This study was a cross sectional one, conducted at Leprosy Hospital, Sarol, Chamba, Himachal Pradesh over a period of two months, May and June 2018. The study used convenient sampling and all 20 disabled patients who were receiving treatment at Leprosy Hospital were included in the study. Socio demographic data which included age, marital status, occupation, type and duration of disability was collected and analyzed. To screen for activity limitation and safety awareness SALSA scale was used. A score of 25 or more points is indicative of activity limitation and disability. Results: In total 20 patients were evaluated, out of which 12 were male and 8 female and the mean age of patients was 51years. Around 90% of female patients were illiterate and financially dependent while on the contrary 90% male patients were literate and financially independent. All the patients presented with some or severe disability according to Salsa scale. There was significant association of age, education, marital status and employment status with disability. Conclusions: Inspite of elimination of leprosy in India, cases of disability and deformity have not declined as expected. Awareness about warning signs among patients and timely diagnosis by health professionals can curb cases of disability among leprosy patients.